2006
DOI: 10.1007/s00428-006-0261-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased numbers of osteoclasts expressing cysteine proteinase cathepsin K in patients with infected osteoradionecrosis and bisphosphonate-associated osteonecrosis—a paradoxical observation?

Abstract: Erosion of the bone is a common problem in patients suffering from infected osteoradionecrosis (IORN) or bisphosphonate-associated osteonecrosis (BON). Besides inflammatory mechanisms and infectious agents, osteoclasts were recently suggested to be specifically involved in the osteolytic mechanisms. We therefore investigated the immunohistochemical labeling of the cysteine proteinase cathepsin K, which plays a central role in osteoclast-mediated bone resorption, in tissue specimens of patients with BON (n=9; f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 34 publications
4
21
1
Order By: Relevance
“…However, it was also demonstrated in vivo that radiation exposure might elicit a pro-resorptive state that is associated with high numbers of osteoclasts [63]. Comparative osteoclast counts in jaw bone sections of ORN and MRONJ (BP) patients have already been described in literature [64]. In accordance with the data of the present study, they found lower numbers of osteoclasts in ORN specimens than in MRONJ (BP) specimens (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, it was also demonstrated in vivo that radiation exposure might elicit a pro-resorptive state that is associated with high numbers of osteoclasts [63]. Comparative osteoclast counts in jaw bone sections of ORN and MRONJ (BP) patients have already been described in literature [64]. In accordance with the data of the present study, they found lower numbers of osteoclasts in ORN specimens than in MRONJ (BP) specimens (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with the data of the present study, they found lower numbers of osteoclasts in ORN specimens than in MRONJ (BP) specimens (Fig. 2b) [64]. However, contrary to the present study, they demonstrated significantly higher numbers of osteoclasts in both types of osteonecrosis when compared with a control group [64].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The subgroups are briefly described in the following paragraphs. It should be mentioned that several of the patients belonging to group I or II were already described in previous studies [11][12][13][14].…”
Section: Patient Datamentioning
confidence: 96%
“…The presence of bacteria, and Actinomyces species in particular, are frequently observed in cultures and histology from ONJ lesion specimens. 20 Hyperbaric oxygen therapy (HBO) has proven beneficial clinically to enhance ORN wound healing and to prevent ORN before surgery in irradiated jaws. HBO produces reactive oxygen and nitrogen species, thereby promoting fibroplasia and angiogenesis by the increase in tissue oxygen gradients and modulating oxygen-sensitive signalling processes critical to osteoclast function.…”
Section: Review Of Bisphosphonates In Dentistrymentioning
confidence: 99%